2010
DOI: 10.3233/jad-2010-091054
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Activation During a Verbal Working Memory Task in Subjects with Amnestic Mild Cognitive Impairment

Abstract: In subjects with Mild Cognitive Impairment (MCI) memory disorders indicate a high risk for conversion to Alzheimer's disease (AD). The objective of this study was to delineate the differences in brain activation between amnestic MCI and age-matched healthy controls (HC) during a verbal working memory task. The verbal working memory task was a delay match to sample design. Brain activation was measured using functional magnetic resonance imaging. There were 8 subjects in each group and were matched for performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 76 publications
(97 reference statements)
7
53
1
Order By: Relevance
“…Lesion studies on humans also showed that patients with medial temporal lobe damages had WM impairment (Ezzyat and Olson, 2008;Olson et al, 2006a,b). Functional MRI studies confirmed that the hippocampus was recruited for WM processing (Davachi and Wagner, 2002;Faraco et al, 2010;Karlsgodt et al, 2005;Toepper et al, 2010), and that hippocampal activation was significantly correlated with WM performance (Berent-Spillson et al, 2010;McGettigan et al, 2011) and/or WM response time (Bokde et al, 2010). Finally, a neural network study reported that the hippocampus was included in a network underlying the maintenance of WM (Gazzaley et al, 2004), suggesting a functional contribution of the hippocampus to WM.…”
Section: Introductionmentioning
confidence: 75%
“…Lesion studies on humans also showed that patients with medial temporal lobe damages had WM impairment (Ezzyat and Olson, 2008;Olson et al, 2006a,b). Functional MRI studies confirmed that the hippocampus was recruited for WM processing (Davachi and Wagner, 2002;Faraco et al, 2010;Karlsgodt et al, 2005;Toepper et al, 2010), and that hippocampal activation was significantly correlated with WM performance (Berent-Spillson et al, 2010;McGettigan et al, 2011) and/or WM response time (Bokde et al, 2010). Finally, a neural network study reported that the hippocampus was included in a network underlying the maintenance of WM (Gazzaley et al, 2004), suggesting a functional contribution of the hippocampus to WM.…”
Section: Introductionmentioning
confidence: 75%
“…These findings indicate that with increasing task difficulty, additional frontal brain regions might have been recruited to play compensatory roles to complete the harder task. In general, the MFG plays a key role in maintaining information and supporting executive function during WM (33), and the SFG is recruited during object location in WM (34). In particular, results from a previous report indicated that gray matter density loss in the bilateral medial frontal gyrus and SFG of type 1 diabetic patients is significantly related to the severity of retinopathy, a common diabetes complication (35).…”
Section: Discussionmentioning
confidence: 97%
“…Speech recognition in noise was generally worse in both elderly groups compared with young individuals. The low tolerance of noise during speech recognition is a common finding in subjects with age-related hearing loss, and the cause may be related to defects of central auditory processing [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . As shown by our data, while normal young subjects do benefit from temporal fluctuation of ICRA noise and yet more consistently from the masking produced by continuous discourse, elderly subjects seem less capable of taking advantage of the masking envelope discontinuities, and this was much more evident in MCI subjects.…”
Section: Discussionmentioning
confidence: 99%